Corrosion behavior of ASTM 1045 mild steel in palm biodiesel. (September 2015) - Jin, Dingfeng; Zhou, Xuehua; Wu, Panpan; Jiang, Li; Ge, Hongliang
Abstract: Corrosive characteristics of biodiesel are important for long-term durability of engine parts. The effect of palm biodiesel on corrosion properties of ASTM 1045 mild steel was studied and compared with that of commercial diesel fuel (0# diesel). Static immersion tests were carried out at different temperatures (27, 50 and 80 °C) for 30, 60 and 120 d. The morphology and composition of corrosion products were characterized by SEM, FT-IR, XRD and XPS. The total acid number was used to investigate the change in acidity of fuel upon exposure. It was found that palm biodiesel is more corrosive than 0# diesel. Temperature and exposure time have critical impact on metal corrosion and degradation of fuels. Graphical abstract: Highlights: Palm biodiesel represent the faster corrosion rate to ASTM 1045 mild steel. Corrosion will be more seriously with increasing temperature and exposure time. Iron compounds appear on the surface of ASTM 1045 mild steel after immersed.